Phyllanthus acidus (L.) Skeels: A review of its traditional uses, phytochemistry, and pharmacological properties. (10th May 2020) - Tan, Siow-Ping; Tan, Eric Nyak-Yong; Lim, Qian-Yu; Nafiah, Mohd Azlan
Abstract: Ethnopharmacological relevance: Phyllanthus acidus (L.) Skeels is not only used for its edible fruits but also used to treat a wide spectrum of diseases such as inflammatory, rheumatism, bronchitis, asthma, respiratory disorder, hepatic diseases and diabetes in India, Asia, the Caribbean region, and Central and South America. This paper aims to discuss the current understanding regarding the traditional uses, phytochemical and pharmacological studies of P. acidus, and their possible research opportunities. Materials and methods: All information on P. acidus was collected from various electronic database (ACS, PubMed, Scopus, Web of Science, SciFinder, Science Direct, Google Scholar, Springer, Wiley, Taylor and Mendeley) and also from those published materials (Ph.D. and M.Sc. dissertations and books) by using a combination of various meaningful keywords. Results: Phytochemical analyses on barks, leaves, roots and fruits of P. acidus identified triterpene, diterpene, sesquiterpene, and glycosides as predominant classes of bioactive substances found in this plant. P. acidus was reported with various pharmacological activities such as in vivo hepatoprotective and hypoglycemic, in vitro anti-oxidant, α-glucosidase inhibitory, anti-inflammatory and antimicrobial activities. However, none of these studies are with clinical research. Some of the studies were performed with only a single set of experiments or with a high dose of extract, and thus the validity of the experimental data may be questionable. In addition, most of the studies described were without identifying the effective components. Some of the assays were even without a positive control for comparison which makes results questionable. Conclusion: Although P. acidus has been proven as a valuable medicinal source from its traditional uses. However, the pharmacological experiments conducted were not sufficient to verify its traditional uses. More investigation is required to confirm the traditional claims such as bioassay-guided isolation of bioactive compounds, detailed pharmacological investigations, clinical studies, and its toxicity investigation. Additionally, an experimental design with sufficient data replication, the use of controls and authenticated research materials, and the selection of a rationale dose or concentration for the analysis are keys to providing reproducible experimental data. Graphical abstract: Image 1